Exploitation of Inland-Breeding Antarctic Petrels by South Polar Skuas - Brooke, Michael de L; Keith, Dave; Røv, Nils (Oecologia, 1999)
During the austral summer of 1996/1997 we studied south polar skuas at Svarthamaren, Dronning Maud Land, Antarctica, where the world's largest known colony of Antarctic petrels is found. Our censuses suggested approximately 250 full-grown skuas and 140,000 breeding pairs of petrels were present. During their breeding season, skuas did not visit the open sea at least 200 km from the site; they relied entirely on prey caught and scavenged from the petrel colony. Because the site is so isolated, we asked whether the prey (petrels) had swamped the predators (skuas), or whether there was evidence that predator numbers were limited by the size of the prey population. Particularly at the end of the petrel incubation period, we found a close correspondence between the energy required by adult skuas and their chicks, ascertained from time budget studies, and the rate at which petrel eggs disappeared from the colony. This suggests that, in this closed system, the predator population was limited by the prey population, and that predator swamping was not an advantage that petrels gained by nesting in this remote location.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

The influence of ornithogenic products on the nutrient status of soils surrounding nests on nunataks in Dronning Maud Land, Antarctica - Cocks, Martin P; Harris, Jean M; Steele, William K; Balfour, Dave A (Polar Research, 1999)
Keywords: Dronning Maud Land; fugler; nunataker; næringsstoff; ornitologi; petreller

Combined use of field observations and SAR interferometry to study ice dynamics and mass balance in Dronning Maud Land, Antarctica - Dietrich, Reinhard; Metzig, Robert; Korth, Wilfried; Perlt, James (Polar Research, 1999)
In the region of the Schirmacheroase (71 °S, 12°E) various geodetic and glaciological research activities have been carried out in the last decade. Several times three geodetic-glaciological traverses were undertaken to study ice velocity, accumulation and ablation, and ice surface height changes. Repeated ground surveys show a significant decrease in surface heights by about 15 cm/y for a large blue-ice area. This paper presents the first interferometrically derived ice velocity field of the inland ice close to the Schirmacheroase. The interferometric analysis of the synthetic aperture radar (SAR) data is performed in combination with ground-based information. Since only ERS-1&2 tandem mission image couples are available for this region a digital elevation model (DEM) is used to remove the effect of topography. Ice velocities up to 100 m/y are proved interferometrically for this part of the inland ice.
Keywords: Dronning Maud Land; geodesi; glasiologi; innlandsis

Variability in snow layering and snow chemistry in the vicinity of two drill sites in western Dronning Maud Land, Antarctica - Hansson, Margareta; Holmlund, Per; Karlöf, Lars; Stenberg, Malin (Annals of Glaciology, 1999)
As part of the pre-site survey in Dronning Maud Land for the European Project for Ice Goring in Antarctica (EPICA), the spatial variability of snow-layer thickness and snow chemistry was studied at two geographically different ice-core drill sites. The study aimed to quantify error bars on accumulation rates derived from firn and ice cores. One site is located on the polar plateau at Amundsenisen (76° S, 8° W) and the other in the coastal area at Maudheimvidda (73° S, 13° W). Medium-deep ice cores (100 m) and shallow firn cores (10-20 m) were drilled and snow pits (0.5-2 5 m) were dug at each site. At Amundsenisen a large (16 m x 6 m x 2.5 m deep) snow pit was dug. Snow structure in this large snow pit was mapped using optical surveying equipment, and photographically documented. Samples for analysis of nine ions and oxygen isotopes were collected along one depth profile. Density and in situ electrical conductivity measurements were made along three depth profiles! Snow-layer variability was studied in two different areas and at two different scales. At a regional scale, measured by snow-radar soundings, the variability was 8% on the polar plateau and 45% in the coastal area. The variability at a micro-scale in the large snow pit was 9%. The results indicate that ice cores from the polar plateau are more representative for a larger area than ice cores drilled in the coastal area There is no doubt that there are significant error bars on high-resolution accumulation data received from firn and ice cores, especially from the coastal area, but averaging over tens of years reduces the error in accumulation estimates.
Keywords: Dronning Maud Land; fysisk geografi; geokjemi; glasiologi; iskjerner; paleoklimatologi

Accumulation and proxy-temperature variability in Dronning Maud Land, Antarctica, determined from shallow firn cores - Isaksson, Elisabeth; van den Broeke, Michiel R; Winther, Jan-Gunnar; Karlöf, Lars; Francis Pinglot, Jean; Gundestrup, Niels (Annals of Glaciology, 1999)
During 1996-97 a European Project for Ice Goring in Antarctica (EPIGA) pre-site surveying traverse worked in the area between 70° S, 5° E and 75° S, 15° E in Dronning Maud Land. We present data obtained from 10 and 20 m deep firn cores drilled between the coast and 600 km inland (to 3450 m a.s.l.). The cores were analyzed for electrical conductivity measurements and total β activity to obtain accumulation data between known time horizons. In addition, some of the cores were analyzed for oxygen isotopes. Annual accumulation varies from 271 mm we. at Fimbulisen to 24 mm we at 2840 m a.s.l. Accumulation at core sites 2400-3000 m a.s.l. has increased by 16-48% since 1965 compared to the 1955-65 period. However, the core sites above 3250 m a.s.l. and one core location on the ice shelf show a decrease during the same period. Furthermore, no change can be detected at the most inland site for the period 1815-1996. In all the cores the last few years seem to have been some of the warmest in these records.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

EPICA Dronning Maud Land pre-site survey - Karlöf, Lars; Gjerde, Knut; Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; geodesi; innlandsis; topografi

Meltwater production in Antarctic blue-ice areas: sensitivity to changes in atmospheric forcing - Liston, Glen E.; Bruland, Oddbjørn; Winther, Jan-Gunnar; Elvehøy, Hallgeir; Sand, Knut (Polar Research, 1999)
In the near coastal regions of Dronning Maud Land, Antarctica, below-surface ice-melt in blue-ice areas has been observed. The low scattering coefficients of the large-grained blue-ice allow penetration of solar radiation, thus providing an energy source below the ice surface. The sub-surface meltwater is significant enough to show up on remote-sensing imagery in the form of ice-covered lakes. Adjacent snow-accumulation areas have much higher scattering coefficients and consequently limit solar radiation penetration in these regions. These snow and ice surfaces are generally below freezing, and little surface melting occurs. To assess the response of these melt features to changes in atmospheric forcings such as cloudiness, air temperature, and snow accumulation, a physically-based model of the coupled atmosphere, radiation, snow, and blue-ice system has been developed. The model consists of a heat transfer equation with a spectrally-dependent solar-radiation source term. The penetration of radiation into the snow and blue-ice depends on the surface albedo, and the snow and blue-ice grain size and density. Model simulations show that ice melt occurring in this area is sensitive to potential variations in atmospheric forcing. Under certain conditions more traditional surface melting occurs and, under other conditions, the existing melt processes can be shut down completely. In light of the sensitivity of this system to variations in atmospheric forcing, and the ability to view melt-related features using remote sensing, a tool exists to efficiently monitor variations in Antarctic coastal climate.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; glasiologi; innlandsis; isshelf; smelting

Studies of seabirds at Svarthamaren - Tveraa, Torkild; Andreassen, Cecilie; Christensen, Guttorm N (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; fugler; ornitologi; petreller

Distribution and Abundance of the Antarctic Petrel - van Franeker, J. A.; Gavrilo, M.; Mehlum, Fridtjof; Veit, R. R.; Woehler, E. J. (Waterbirds: The International Journal of Waterbird Biology, 1999)
Published and unpublished information on the distribution and abundance of the Antarctic Petrel (Thalassoica antarctica) is reviewed. Currently 35 colonies with approximately half a million breeding pairs are known. All but one of these known colonies are situated in East Antarctica. However, an estimate derived from at sea studies in three of four apparent centers of oceanic occurrence suggests a population as high as four to seven million breeding pairs (10 to 20 million individuals). In spite of the tentative nature of such an estimate, the difference with the colony-derived figure strongly suggests the existence of large, currently undiscovered colonies, particularly in western Antarctica and Victoria Land, where a complete mismatch exists between bird observations at sea and known colonies. In eastern Antarctica, in addition to undiscovered colonies, some known ones could be considerably larger than currently documented.
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; petreller; zoologi